When Performance Becomes Pedagogy: Analyzing Music Education Students’ Attraction to the Stage - Riyan Hidayatullah; Fajar Riyantika; Try Wahyu Purnomo (Harmonia: Journal of Arts Research and Education, 2026)
At its core, performance-based learning is an important aspect of music education in the classroom. Performance provides students with additional opportunities beyond artistic expression to bond and engage with their peers. This project seeks to identify how performance-based learning cultivates relationships with a primary emphasis on students who are socially oriented. Through observations, interviews, and reflections, the research shows that students’ informal socialization during performance builds their musicianship, makes them more communicative and better collaborative partners. The results indicate that the more performance opportunities are arranged and the more unplanned socialization is tolerated, the better students are at musicianship and the better their relationships with peers. This study shows the importance of using performance as an opportunity for learning that links the formal and informal aspects of teaching and socialization, and provides substantial information on performance for the construction of the music curriculum.